PENGARUH ARUS KAS INVESTASI, LABA AKUNTANSI DAN FINANCIAL DISTRESS TERHADAP RETURN SAHAM - Suryani Rahma; Rahma, Ayumi (Publika Citra Media, 2025)
A stock return is a profit obtained by stock investors from funds that have been invested in making investments. This study aims to determine the effect of Investment Cash Flow, Accounting Profit, and Financial Distress on Stock Returns. This study was conducted in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2023 period. The population in this study was 125 companies. The sample was selected using a purposive sampling technique that selects companies with several criteria, so that the total sample obtained was 38 companies. The method used in analyzing the effect of independent variables on dependents in this study is panel data regression analysis using a purposive sampling technique that selects companies with criteria, so that the total sample obtained is 26 companies. The method used in analyzing the effect of independent variables on dependents in this study is panel data regression analysis using Eviews 12 software. The results of this study indicate that investment cash flow has a significant effect on stock returns, accounting profit does not have a significant effect on stock returns, Financial Distress does not have a significant effect on stock returns, and has a significant effect on stock returns simultaneously.